Acute Coronary Syndrome - reinfarction predictors and outcomes. (11th May 2021) - Santos, M; Santos, H; Almeida, I; Miranda, H; Sa, C; Chin, J; Almeida, S; Sousa, C; Tavares, J; Santos, L; Almeida, ML
Abstract: Funding Acknowledgements: Type of funding sources: None. OnBehalf: on behalf of the Investigators of " Portuguese Registry of ACS " Introduction: Reinfarction (RI) is a potential complication of acute coronary syndromes (ACS) and it is, therefore, important to access its impact on prognosis and identify patients with higher risk of RI in the setting of ACS. Objective: To evaluate predictors and prognosis of RI in the setting of ACS. Methods: Based on a multicenter retrospective study, data collected from admissions between 1/10/2010 and 4/09/2019. Patients (pts) without data on previous cardiovascular history or uncompleted clinical data were excluded. Pts were divided in 2 groups (G): GA – pts without RI; GB - pts with RI during hospitalization. Logistic regression and survival analysis were performed. Results: Between 25718 pts with ACS, RI occurred in 223 (0.87%). Regarding epidemiological factors and past history, GB was older (70 ± 12 vs 67 ± 14, p < 0.001), had higher rates of hypertension (77.4% vs 70.6%, p = 0.028), previous stroke (12.1% vs 7.2%, p = 0.005), peripheric arterial disease (10.0% vs 5.5%, p = 0.004) and chronic obstructive pulmonary disease (8.6% vs 4.4%, p = 0.003). GB had higher rates of non-ST-elevation myocardial infarction (MI) (54.3% vs 45.9%, p = 0.012) and GA had higher rates of ST-elevation MI (42.4% vs 35.9%, p = 0.049). The groups were similar regarding blood pressure (p = 0.285), heart rate (p = 0.796) and Killip-Kimball class at admission, but GB had higher levels of brain natriuretic peptide (392 vs 180, p = 0.005). GB had higher rates of multivessel disease (62.8% vs 51.6%, p = 0.002), left ventricle dysfunction (50.0% vs 39.1%, p = 0.002), higher needs of mechanical ventilation (6.3% and vs 1.9%, p < 0.001) non-invasive ventilation (5.4% vs 1.7%, p < 0.001). Logistic regression confirmed that peripheric arterial disease (p = 0.011, OR 1.93, CI 1.17-3.19), multivessel disease (p = 0.003, OR 1.69, CI 1.20-2.39) and lower left ventricle function (p < 0.001, OR 2.42, CI 1.69-3.47) were predictors of RI in the setting of ACS. Event-free survival was similar between groups (p = 0.399). Conclusion: RI in the setting of ACS was associated multivessel disease and left ventricle disfunction, however, 1-year prognosis was similar to pts who didn't suffer RI.